2019
DOI: 10.1021/acsanm.9b01309
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen–Sulfur-Doped Graphene Quantum Dots with Metal Ion-Resistance for Bioimaging

Abstract: The development of ultrastable and highly fluorescent heteroatoms-doped graphene quantum dots (GQDs) for bioimaging remains a challenge due to the fluorescence quenching caused by binding between the heteroatoms-based functional groups of the GQDs and common metal ions in biological systems. Here, we developed a facile hydrothermal method to prepare nitrogen−sulfur doped GQDs (NS-GQDs). The fluorescence signals of the NS-GQDs are highly stable in the existence of different metal ions. Two natural products, asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Reproduced with permission from Ref. (Schroer et al, 2019). Copyright 2019 American Chemical Society.…”
Section: The Application Of Qds To Cell Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission from Ref. (Schroer et al, 2019). Copyright 2019 American Chemical Society.…”
Section: The Application Of Qds To Cell Imagingmentioning
confidence: 99%
“…In recent years, due to the great potential of GQDs and Cdots in the field of bioimging, scientists have made great efforts to improve their fluorescence properties, such as doping nitrogen or sulfur into these QDs (Lu, Li, Dong, & Wei, 2019; Shi et al, 2019). However, the fluorescence is easily quenched by metal ions, which is one of the challenges of biological imaging of carbon‐based QDs (Schroer et al, 2019). Fortunately, scientists are improving their properties step by step.…”
Section: The Application Of Qds To Cell Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the CDs synthesized in our study showed outstanding photo‐, ions‐ and time‐stability, providing particularly suitable for practical applications including bio‐imaging, anticounterfeiting, biomedicine, sensor, and so on. The high‐stability of CDs is due to various functional groups attached to the surfaces of CDs 60,65 …”
Section: Resultsmentioning
confidence: 99%
“…The high-stability of CDs is due to various functional groups attached to the surfaces of CDs. 60,65…”
Section: High Stability Of the Cdsmentioning
confidence: 99%